PENGARUH KEPERCAYAAN, KEMUDAHAN DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN DARING DI APLIKASI BUKALAPAK PADA MAHASISWA POLITEKNIK NEGERI BATAM - Hendra Gunawan; Kartika Ayuningtiyas (Politeknik Negeri Batam, 2018)
The purpose of this study was to determine and analyze the influence of trust, ease of use and information quality on the purchasing decision. The sample are students who ever made purchases online. The sampling method using purposive sampling and used multiple regression analysis. The results show that simultaneously, trust, ease of use and information quality are affecting positively and significantly in the purchasing decision. Partially, trust is affecting not significantly in the purchasing decision in online shop. Ease of use and information quality are affecting positively in the purchasing decision in online shop.